Child sexual abuse and consequences in adult life: a systematic review (Research, Society and Development, 2020)
Introduction: Childhood sexual abuse manifests itself in all countries and cultures, bringing consequences that can remain until adulthood, affecting the physical and especially psychological health of the individual. Objectives: The present study aimed to investigate in the literature what are the psychological consequences acquired by adults abused in childhood. Method: It is a qualitative, descriptive, exploratory research and review of systematic literature, whose survey took place through the database of scientific articles called BIREME, in the period from 2014 to 2019, using as or descriptor or term Abuse child sexuality. Based on this research, among the 120 articles presented by the database. Results: after applying all inclusion criteria and excluding 9 articles, were selected that deal with the problem. Discussion: This study allowed us to observe that the consequences of sexual abuse in childhood imply serious damage to the mental health of the victims, and, if not properly allowed, can remain for life. Conclusion: The proportion of damages depends a lot on the child's age, the configuration of the relationship in which there is between the abuser and the victim, having sex, frequency, and also, the duration of the sexual abuse. The younger the child, the more vulnerable he is to trauma.